Bibliometric Analysis on Global Research Trends of Airborne Microorganisms in Recent Ten Years (2011–2020) - Yonghao Jia; Yihan Chen; Ping Yan; Qianli Huang (Aerosol and Air Quality Research)
Abstract In recent years, exposure to bioaerosols—airborne particles of biological origin—has become a significant public health concern. Hence, this study aims to provide a bibliometric analysis of global trends in research on airborne microorganisms in the last ten years (2011–2020). Using the Web of Science (WoS) Core Collection database, a total of 1087 articles published during this period were selected for analysis. Firstly, we identified 11 co-citation clusters: potential pan microbiome, bioaerosol science, beneficial microbe, urban area, fungal microbiota, wastewater treatment plant, airborne microbial aerosol, modern practice, facilities—a review, airborne microbial biodiversity, and acidic electrolyzed water. Based on the co-occurrence between keywords in this literature, we concluded that particle-attached microorganisms, community structures of urban airborne microbes, and biological aerosols have inspired the hotspots in research during recent years, which suggests that bioaerosols are currently a popular topic in the field of air microbiology, with bacteria being the most frequently studied airborne microorganisms. We also discovered that interest in coronavirus disease 2019 (COVID-19) has continually risen during the past eight months, with the number of relevant articles exceeding 19,880, of which 106 have been frequently cited. Analyzing 500 recent publications on this topic, we found a high co-occurrence of COVID-19, pandemic, and coronavirus as well as of anxiety, depression, and stress. The greatest number of articles on airborne microorganisms in the last decade have been contributed by the USA, followed by China and France. Moreover, according to this metric, the leading institutions are Colorado State University and Peking University, and the top three journals are Applied and Environmental Microbiology, Atmospheric Environment, and Science of the Total Environment. The annual publication volume for this subject shows an increasing trend, indicating that interest in airborne microorganisms continues to grow. Our bibliometric analysis reveals the recent research hotspots and topic trends in air microbiology, thus offering potential clues for further examination.